Website Performance Evaluation by Grey Relational Analysis: A Research on Companies in BIST Technology and Informatics Index - Başeğmez, Hülya; Özdemir, Kadir (My University, 2023)
Since websites are the visible face of companies, they are a significant determinant of how customers perceive interactions. Websites give the first impression of ensuring customer satisfaction and meeting expectations. Therefore, a quality website will provide competitive advantages. In this study, the website performance of 27 businesses in the BIST Technology and Informatics Index was evaluated, and 24 websites were analysed because the websites of three companies gave analysis errors. Website performance was measured by Page Size (Mb), Onload Time (s), First contentful paint (ms), Performance Score (%), Largest Contentful Paint (ms), Total Blocking Time (ms) and Speed Index (ms) criteria. The performance evaluation criteria of the websites were determined based on the literature and expert opinion. The data of the websites were obtained from GTmetrix automated test tool and analysed by using the Grey Relational Analysis (GRA) method. As a result of the analysis, companies’ websites were ranked according to their performance score. Accordingly, Alcatel-Lucent, Plastik Kart, Escort, Smartiks, and Papilon have the highest website performance scores and are in the top five. Aselsan, Index, Datagate, Despec and Mia Teknoloji have the lowest performance scores.
Keywords: Grey Relational Analysis (GRA); Website performance evaluation; GTmetrix